TRADISI BASOLANG MASYARAKAT SUKU TALANG MAMAK - Lestari, Reni Dian; Putra, M. Jaya Adi; Erlisnawati, Erlisnawati (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2022)
Abstract: Tradition is a habit in which there is knowledge, understanding, beliefs and habits that guide people in carrying out their lives. Tradition has an important meaning for the life of a particular society. The tradition that is still maintained in the life of the Talang Mamak tribe is the Basolang tradition. The purpose of conducting the research is to analyze the Basolang tradition of the Talang Mamak tribal community. The type of research used in this study are ethnographic research methods incorporated into qualitative research. The source of data in this study is the Talang Mamak tribal community. Data collection methods used are observation, interviews and documentation. The data analysis technique used is data reduction, data presentation and drawing conclusions. The results of this research indicate that the Basolang tradition is an agricultural activity with various activities. The process of activities in the Basolang tradition is carried out according to the customary rules and beliefs of the Talang Mamak tribe that have been in effect since the time of the ancestors until now. This is apparent from the results of interviews conducted by researchers with the Talang Mamak tribal community.Key Words: Basolang Tradition, Talang Mamak Tribe Society